English Majors’ Perceptions of Autonomous Learning Skills and Their Writing Performance in an E-portfolio-based Writing Course - Duong My Tham, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This paper aimed to scrutinize English majors’ perceptions of autonomous learning skills and explore whether or not their writing skills improved after a 15-week writing course with the employment of an e-portfolio as a learning tool. This mixed-methods study involved thirty-five English majors at a Vietnamese university in doing the mid-term test and final test and reporting their writing progress as well as their autonomous learning in the writing logs throughout the course and during the individual semi-structured interviews. The quantitative data were statistically processed using SPSS in terms of descriptive statistics and Wilcoxon signed rank test, and the data obtained from the interviews and writing logs were analyzed through the content analysis approach. The findings indicated the significant improvement in the English majors’ writing skills. Furthermore, the participants had positive attitudes toward the autonomous learning skills (e.g., setting learning goals, choosing learning materials, creating a study plan, writing reflections, and conducting peer assessment) except for the hesitation in conducting self-assessment during the training course.Received 9thDecember 2020; Revised 2nd May 2021; Accepted 20th June 2021